Implantação de Sistema Integrado de Gestão: estudo de caso em universidade pública - Oliveira Júnior, José Martins de (2019)
The deployment and use of ERP - Enterprise Resource Planning systems remains challenging as user and manager satisfaction levels with results are lower than desired. The proposal for the modernization of Information and Communication Technologies at the State University of Maranhão offered an opportunity for descriptive research to monitor and analyze the results achieved, the processes used, the challenges and difficulties faced. Seeking to identify the influencing factors and weigh the importance of each of them in the results obtained. During the case study, all available project documentation was considered, including interviews and observation notes, as well as questionnaires were applied to a group of users involved in the implementation, generating a qualitative perception of the implementation process.